1988
DOI: 10.1007/bf00266972
|View full text |Cite
|
Sign up to set email alerts
|

The role of the coracoacromial ligament in the impingement syndrome

Abstract: Seventeen patients with a painful arc syndrome and tenderness over the coracoacromial ligament were selected to demonstrate the changes in the coracoacromial ligament in the impingement syndrome. Plain X-ray examination was normal and a preoperative subacromial bursogram demonstrated impingement in only three out of 17 patients. However, at operation the subacromial space under the coracoacromial ligament, which normally admits the tip of the little finger, appeared unusually tight and barely accessible in 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
4

Year Published

1996
1996
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(26 citation statements)
references
References 11 publications
0
22
0
4
Order By: Relevance
“…6,22,24,31 In the current study, 22 (92%) of 24 patients with articular-side tears showed pathologic changes in the acromion, and the pathologic changes were significantly milder in patients with articular side tears compared with bursal side tears (P Ͻ .001) (Tables II and III). Although differentiating between tendinosis and a partial tear with MRI is difficult, it is a noninvasive technique with the ability to define reliably pathologic changes that are associated with chronic impingement, such as tendinitis or degeneration of the tendon (Figure 4).…”
Section: Discussionmentioning
confidence: 72%
“…6,22,24,31 In the current study, 22 (92%) of 24 patients with articular-side tears showed pathologic changes in the acromion, and the pathologic changes were significantly milder in patients with articular side tears compared with bursal side tears (P Ͻ .001) (Tables II and III). Although differentiating between tendinosis and a partial tear with MRI is difficult, it is a noninvasive technique with the ability to define reliably pathologic changes that are associated with chronic impingement, such as tendinitis or degeneration of the tendon (Figure 4).…”
Section: Discussionmentioning
confidence: 72%
“…The ligament thus completes the coracoacromial arch, which has been described and implicated in shoulder pathology. 6,9,12,13,21,25,30,32 Brodie 2 first described the CAL differentiating into two distinct bands or ligaments that attach at different points on the coracoid process and noted that these two bands are separated by a diaphanous membrane. These distinguishable bands of the CAL were described as medial and lateral, the lateral band being stronger and thicker than the medial band.…”
mentioning
confidence: 99%
“…1,3,4,8,9,14,17,20,21,25,27,28,30,31 The CAL may form a small ridge at the inferolateral margin of the acromion that contributes toward rotator cuff pathology. Acromion enthesopathy (spur formation within the CAL at the anterior margin of the acromion) has been attributed to forces transmitted through the CAL via traction.…”
mentioning
confidence: 99%
“…Les tendinopathies non rompues non calcifiantes de la coiffe des rotateurs représentent l'indication essentielle [5][6][7][8]. Cependant, les résultats doivent être nuancés en fonction des lésions anatomopathologiques rencontrées :…”
Section: Indicationsunclassified